2018
DOI: 10.1515/chem-2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

The Optical and Crystallite Characterization of Bilayer TiO2 Films Coated on Different ITO layers

Abstract: Titanium dioxide(TiO2) is a well-known material which is non-toxic with efficient photoactivity, high stability, low-cost and corrosion-resistant. Up to today’s technology, TiO2 films are coated for various applications in the scientific area. In this study, bilayer TiO2 films were coated on indium tin oxide(ITO) layers that have different characteristic properties. The devices designed as homemade of Direct Current Magnetron Sputtering (DCMS) and Spray Pyrolysis Deposition (SPD) coating methods were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 34–37 ] In brief, the loaded FeS 2 (lower valence) will interact with higher valence parent cations of TiO 2 NTs intrinsically generate oxygen vacancies, which alter the overall symmetry of FeS 2 @TiO 2 NTs, resulting in the variation of Raman peaks position as well as intensities (Figure 4). [ 51 ] As the loading amount of FeS 2 is increased, the TiO 2 NTs' peak intensities increased due to the homogeneous loading and uniform distribution of FeS 2 . Compared to pure‐TiO 2 NTs, 05‐FeS 2 @TiO 2 NTs, and 10‐FeS 2 @TiO 2 NTs, the high‐intensity peaks were seen for 15‐FeS 2 @TiO 2 NTs and 20‐FeS 2 @TiO 2 NTs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34–37 ] In brief, the loaded FeS 2 (lower valence) will interact with higher valence parent cations of TiO 2 NTs intrinsically generate oxygen vacancies, which alter the overall symmetry of FeS 2 @TiO 2 NTs, resulting in the variation of Raman peaks position as well as intensities (Figure 4). [ 51 ] As the loading amount of FeS 2 is increased, the TiO 2 NTs' peak intensities increased due to the homogeneous loading and uniform distribution of FeS 2 . Compared to pure‐TiO 2 NTs, 05‐FeS 2 @TiO 2 NTs, and 10‐FeS 2 @TiO 2 NTs, the high‐intensity peaks were seen for 15‐FeS 2 @TiO 2 NTs and 20‐FeS 2 @TiO 2 NTs.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing TiO 2 wettability, the photocatalyst concentration increases and the number of electron–hole pairs increases because of (i) the absorption of energy from APPJ photons due to the incident light of the non-thermal jet, (ii) APPJ photons overcome the bandgap of TiO 2 , leading to the generation of more active substances that can be absorbed by the cells and cause acceleration of the sterilization efficiency [ 41 , 42 , 43 ]. There are various other reactions arising from light being absorbed by TiO 2 in addition to the reactions mentioned before (Equations (4)–(10)): TiO 2 + hv → (e cb + h vb ) (TiO 2 ) Ti 4+ + e cb → Ti 3+ where e cb is a conduction band electron, h vb is a valence band hole, and Ti 2+ , Ti 3+ , and Ti 4+ are titanium oxidation states.…”
Section: Resultsmentioning
confidence: 99%
“…Literature [28], reported that A-TiO 2 (1 0 1) served as the most stable system. According to the research report, the bilayer TiO 2 film can be realized in the experiment [29]. Therefore, pure bilayers with 72 atoms of R-TiO 2 (1 1 0) model or A-TiO 2 (1 0 1) model were constructed with a 15-Å thick vacuum layer to evade the interaction of neighboring 2D-TiO 2 monolayers in the z-axis direction.…”
Section: Model Constructionmentioning
confidence: 99%